2012
DOI: 10.1007/s10902-012-9384-9
|View full text |Cite
|
Sign up to set email alerts
|

Are Relative-Income Effects Constant Across the Well-Being Distribution?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Typical determinants of subjective wellbeing (income, social life and health) vary over the subjective wellbeing distribution as well, and all are less strongly associated with subjective wellbeing for the happiest quantiles (with considerable heterogeneity also between explanatory variables: for example, the social life variable was still positively associated with subjective wellbeing for the happiest individuals, while income was not; see Binder and Coad , p. 285). In different studies, a positive association (on average) between volunteering and subjective wellbeing turned out to be driven solely by the association found for the unhappiest individuals in the subjective wellbeing distribution (Binder and Freytag ); a similar finding appears to be the case for negative effects of relative income comparisons (Budria ). It can be conjectured that unemployment will also have a heterogeneous impact over the wellbeing distribution.…”
Section: Literature Backgroundmentioning
confidence: 91%
See 3 more Smart Citations
“…Typical determinants of subjective wellbeing (income, social life and health) vary over the subjective wellbeing distribution as well, and all are less strongly associated with subjective wellbeing for the happiest quantiles (with considerable heterogeneity also between explanatory variables: for example, the social life variable was still positively associated with subjective wellbeing for the happiest individuals, while income was not; see Binder and Coad , p. 285). In different studies, a positive association (on average) between volunteering and subjective wellbeing turned out to be driven solely by the association found for the unhappiest individuals in the subjective wellbeing distribution (Binder and Freytag ); a similar finding appears to be the case for negative effects of relative income comparisons (Budria ). It can be conjectured that unemployment will also have a heterogeneous impact over the wellbeing distribution.…”
Section: Literature Backgroundmentioning
confidence: 91%
“…As has been argued in Binder and Coad (), such a focus neglects important information about the extremes of the subjective wellbeing distribution: especially in heterogeneous distributions, regression methodologies that focus on means might seriously underestimate or overestimate effects, or even fail to identify effects at all (Cade and Noon ). Quantile regressions have only recently been introduced to subjective wellbeing research (Binder and Coad ; Binder and Freytag ; see also Budria ) and provide evidence for considerable heterogeneity over the conditional wellbeing distribution (that is, conditional on the independent variables). As discussed in the Introduction, this heterogeneity can account for the absence of an (average) association typically found between education and subjective wellbeing.…”
Section: Literature Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…The economic literature incorporating personality as a source of individual heterogeneity for well‐being is relatively new. Work by Binder and Coad (), Clark et al (), and Budria () revealed differential effects across the well‐being distribution, but offered little insight on why it exists. But other studies showed that personality affects subjective well‐being (Headey ; Myers and Diener ; Rammstedt ; Steel, Schmidt, and Shultz ), and a number of studies have looked at how personality affects coping with diverse life events such as unemployment (Boyce, Wood, and Brown ), income changes (Boyce and Wood ; Budria and Ferrer‐i‐Carbonell ; Soto and Luhmann ), marriage, childbirth and widowhood (Yap, Anusic, and Lucas ), illness (Kesavayuth, Rosenman, and Zikos ), and disability (Boyce and Wood ).…”
Section: Introductionmentioning
confidence: 99%